Forced off Farm? Labor Allocation Response to Land Requisition in Rural China - Shuang Ma; Ren Mu (Institute of Labor Economics (IZA), 2017)
Land requisition has been an important process by which Chinese local governments promote urbanization and generate revenue. This study investigates the impacts of land requisition on farmers' decisions of labor allocation between agricultural and non-agricultural sectors. We argue that, conditional on village fixed effects, land requisition can be explored as a quasi-natural experiment to identify the relationship between land rights and labor allocation of farmers. We find that young farmers (age 16-44) are not affected in their migration decisions by land loss through requisition, while some older farmers (age 45-55) are affected. In response to land loss through requisition, the probability that older farmers living beyond the mean distance from the county seat migrates to cities increases by 8.5 percentage points. An econometric test confirms that the finding is unlikely to be driven by unobserved variables associated with household experience of land loss. This finding raises concerns about the wellbeing of the farmers who may not be competitive in the urban labor market and therefore unlikely to leave farming unless they have to.
Keywords: O12; O15; J61; Q15; R28; 330; land institution; land requisition; migration; urbanization; farmers; China